Assessment of the Relationship Between Impacted Mandibular Third Molars and Inferior Alveolar Nerve With Dental 3-Dimensional Computed Tomography - Nakayama, Keisuke; Nonoyama, Makoto; Takaki, Yasuo; Kagawa, Toyohiro; Yuasa, Kenji; Izumi, Kiwako; Ozeki, Satoru; Ikebe, Tetsuro (Journal of oral and maxillofacial surgery, 2009)
The purpose of this study was to assess the capacity of dental 3-dimensional computed tomography (3D-CT; limited cone-beam CT) to predict the exposure and injury of the inferior alveolar nerve (IAN) after mandibular third molar extractions. This study was a retrospective case series of patients who presented for extraction of mandibular third molars. Subjects eligible for study enrollment were those who underwent preoperative dental 3D-CT because the mandibular third molars were determined to be extremely close to the IAN on panoramic radiogram. The predictive variable was the anatomic relation of the IAN and third molar apices and was a binary variable, contact or noncontact. The primary outcome variable was IAN exposure, and the secondary outcome variable was IAN injury. From January 2006 to August 2007, 1,853 mandibular third molars in 1,539 patients were extracted. Among them, dental 3D-CT was performed on 53 third molars in 47 patients. The mandibular third molars were judged to make contact with the mandibular canal on dental 3D-CT images in 35 cases (66%). Intraoperative IAN exposure was observed in 17 (49%) contact cases and 2 (11%) noncontact cases on dental 3D-CT images. Of 53 cases extracted after dental 3D-CT examinations, IAN injury occurred in 8 cases (15%). IAN exposure led to IAN injury in 36.8% of cases, whereas IAN injury occurred in only 2.9% of cases without IAN exposure. Although the incidence of IAN injury in the molar-canal contact cases was 23%, all 8 cases with IAN injury (100%) were included in these contact cases. When viewing the anatomic relation between the IAN and mandibular third molar root apices using dental 3D-CT, contact of the 2 anatomic structures results in an increased risk for IAN exposure or injury.